Regulatory RNAs and coronary artery calcification: A systematic review of clinical associations and biological insights - Tsuraya, Alfi; Raras, Tri Yudani Mardining; Lestari, Bayu; Ramadhani, Risa; Hose, Victor Alvianoes Guterez; Rohman, Mohammad Saifur; Waranugraha, Yoga; Fajar, Jonny Karunia (Heart Science Journal, 2026)
BACKGROUND: Regulatory RNAs, including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs), have emerged as key regulators of vascular remodelling and coronary heart disease. However, their specific roles in coronary artery calcification (CAC) remain fragmented across diverse clinical studies. OBJECTIVES: This review aims to systematically synthesize human observational evidence on differentially expressed regulatory RNAs associated with CAC and their underlying molecular mechanisms. METHODS: We included clinical observational studies (case-control, cross-sectional, or cohort designs) that compared regulatory RNA expression in patients with and without CAC. We searched PubMed, BioMed Central, Wiley, ScienceDirect, and Cochrane between January 2010 and June 2025. Risk of bias was assessed using the JBI Critical Appraisal Checklist for Observational Studies. Data were synthesized narratively with stratification by RNA type, direction of expression, and biological mechanism. RESULTS: A total of 10 eligible studies were included. Several regulatory RNAs demonstrated potential as biomarkers or modulators of CAC. However, the diversity of regulatory RNAs highlights the complex and multifactorial nature of CAC, while also revealing opportunities for future investigation. CONCLUSION: Notably, circSmad4 demonstrated a favourable trend with a high AUC and a reasonably balanced mix of sensitivity and specificity, despite with relatively larger sample sizes.